How do care farms improve the sleep quality of individuals with psychological disorders? - Keiji Jindo; Reiko Kasama; Nozomu Tanabe (Social Sciences and Humanities Open, 2025)
Sleep quality is crucial for the health of individuals with disabilities. Care farming, also known as social farming, offers health, social, and educational care services to individuals with diverse needs, including those with disabilities and disorders. This study quantitatively examined the relationship between care farming activities and sleep quality among individuals with and without (control) disorders using secondary data provided by a national institution. The dataset was not collected by the research team but included sleep measurements recorded through a validated non-wearable device. Within the group with psychological disorders, this study compared three subgroups (mental, neurodevelopmental, and intellectual disorders) to understand the specific relationship of care farming with sleep quality. Sleep latency, sleep efficiency, and wake after sleep onset (WASO) were analyzed. Compared to those in the control group, individuals with psychological disorders exhibited significantly greater variance in sleep latency and WASO scores. Notably, the group with psychological disorders experienced decreased WASO following farm work compared to non-working days, whereas the control group showed no significant changes. Significant differences in sleep efficiency between the groups were observed on non-working days, suggesting that the gap in sleep performance narrowed after workdays. Sleep quality varied across psychological disorder subgroups: neurodevelopmental disorders were strongly associated with differences in sleep latency and efficiency, whereas individuals with mental and intellectual disorders showed a 6.5-min reduction in WASO on working days. Using quantitative data, the findings indicate a a relatively positive association between farming practices and sleep quality in individuals with psychological disorders who participated in these activities. These findings highlight the importance of considering both psychological disorder types and distinguishing between working and non-working days when evaluating sleep quality.